SHALE GAS POTENTIAL OF KUANTAN FORMATION TABEK PATAH AND SURROUNDING AREAS, SUMATRA BARAT - FEBRI YENI, YULIA
Shale gas is gas contained in the fine grain reservoir and trapped in it. Unlike the conventional hydrocarbons, shale gas does not have to meet the requirements for petroleum system because it does not require migration or cap rock. Kuantan Formation is Carbon Ã‚Â– Perm age rock formation which is part of West Sumatra Block and in the research area can be classified into three units, there are Metamorphic Unit, Shale Unit, and Limestone Unit. Shales of Kuantan Formation deposited on the coastal regions associated with marine environment.